How Large-established Joint Venture Firm Remains Resilient in a Disruptive Era: A Process Tracing Case Study - Tarigan, Moris; Simatupang, Togar Mangihut; Bangun, Yuni Ros (UI Scholars Hub, 2021)
The crises have spread out globally and have impacted industries, either large firms or small firms. These impacts make the firms economically in intense trouble or file bankruptcies and lay off their employees, as their incomes are falling significantly globally. Therefore, this study investigates how businesses can improve their resilience and be prepared to cope with crises and threats in this disruptive era. What were the strategies the firm has implemented? The authors have conducted this research in PT Alpha by using the process Tracing case study method in semi-structured interviews with eight critical respondents in ten in-depth interviews, split into a pilot study and the triangulation period based on those initial inputs. The authors have used process tracing analysis to test the evidence. The results showed that the major businesses need to concentrate on the three phases as a process, i.e., preparation and anticipation, coping and improvisation, and recovery and transformation, to be resilient (it is an enhancement of the concept of Duchek, 2020). To have a more comprehensive view, the authors have extended the research from the economic crises in 1998 and 2008 till 2019; thus, the process-tracing case study is a suitable method. This method has been used a lot for historical settings. This paper recommends further research to expand the studies to other large established companies in similar segments or other segments.